ANALYSIS OF ARTICLE 176 OF LAW NO. 10 OF 2016 REGARDING FILLING OF VACANCY POSITIONS OF DEPUTY REGIONAL HEAD - Hendri. K, Hendri. K; Fikriana, Askana (EKSEKUSI, 2024)
Article 176 paragraphs (1) and (2) of Law No. 10/2016 regulates the mechanism for filling vacancies of deputy governors, deputy regents, and deputy mayors, but in practice there are many delays in filling vacancies of deputy regional head positions. In fact, in some regions there are vacancies until the term of office of the deputy head of the region expires. This research aims to: (1). Analyze the mechanism for filling vacancies of deputy regional heads, (2). Analyze why there is a delay in filling the vacancy of the position of deputy regional head, (3) Offer a legal solution to anticipate the delay in the process of replacing the deputy regional head. Based on how to process data, this research is included in qualitative research. This research is not to find how many vacant deputy regional heads there are in Indonesia. This research also does not use statistical data processing to draw a conclusion. This research is a library research. The type of data in this research is secondary data consisting of primary legal materials and secondary legal materials. The mechanism for filling the vacancy of the regional head by election by the provincial DPRD or regency/city DPRD is based on a proposal from the supporting political party or a coalition of political parties. In practice, it is difficult for the supporting parties to agree to appoint a replacement, and each political party has an interest in making a candidate from the party or candidate they support as deputy regional head. The solution is the need for additional articles in Law No. 10/2016 aimed at anticipating if a political party or coalition of political parties fails to propose two replacement candidates.Keywords: filling positions, deputy regional head.